Old Capitol : portrait of an Iowa landmark - Keyes, Margaret N., 1918-2015 (Bur oak original., 1988)
Built between 1839 and 1842, the domed structure of Iowa City's Old Capitol served as the third territorial capitol and the first state capitol of Iowa. In 1857, when the state government was moved to Des Moines, Old Capitol became the first building of the new University of Iowa. It remains today the centerpiece of this handsome campus. The story of its history and restoration, told in this elegantly illustrated book, is an intriguing account of historical architectural detection. Using primary sources, including manuscripts, vouchers, account books, newspaper stories, correspondence, a.